Cross Country Skiing : Olympic Handbook of Sports Medicine. - Rusko, Heikki (Delete (Olympic Handbook Of Sports Medicine), 2008)
The Handbooks of Sports Medicine and Science present basic clinical and scientific information in a clear style and format as related to specific sports events drawn from the Olympic Summer and Winter Games. Each handbook is written by a small team of authorities co-ordinated by an editor who is internationally respected and recognised in the particular sport activity. Each volume presents up-to-date information on the basic biology of the sport, conditioning techniques, nutrition, and the medical aspects of injury prevention, treatment, and rehabilitation. This Handbook will constitute the mo.